Modern Television Practice Transmission Reception and Applications - Gulati, R. R. n m (India : New age international, 2015)
ew Age International (P) Limited, 2015. Softcover. Condición: New. 5th or later edition. This book has been revised to keep pace with advances in TV technology that have enabled Plasma and LCD receivers and new Projection TV systems. Though the chapters devoted to conventional television, advances in television systems and Digital Satellite Television are retained, many chapters that described applications have been revised to address to newer innovations such as: Printed Pages: 706. Nº de ref. del artículo: 86678
1.Introducction to television 2.. Television picture 3.Television camera 4.Pictue tubes y desarrollo
Incluye bibliografía, glosario e índice analítico
Keywords: ELECTRONICA; BIOLOGIA- ENSEÑANZA